List okólny Inter munera Najwyższego Trybunału Sygnatury Apostolskiej w sprawie stanu i działalności Trybunałów z 30 lipca 2016 r. - Góralski, Wojciech (Ius Matrimoniale, 2018)
The competences of the Supreme Tribunal of the Apostolic Signatura include: watching over the proper administration of justice throughout the Church. This obligation was already sanctioned in the Apostolic Constitution Regimini Ecclesiae universae of Paul VI (1967), previously it belonged to the Congregation for the Discipline of the Sacraments. The Circular Letter of the Supreme Tribunal of 30 July 2016 is an expression of the concern of the Apostolic Signatura for the adjustment to new conditions of the existing regulations in the scope of control over the functioning of ecclesiastical tribunals in the world. The regulations contained in it take into account the change of CIC and CCEO canons in the area of cases of nullity of marriage, made Motu proprio by Francis: Mitis Iudex Dominus Iesus and Mitis et misericors Iesus. The author presents the aforementioned Circular Letter focusing on the following issues: ecclesiological context of marital process reform of 2015, manners of submitting information by the tribunals by submitting annual reports, activities of the Apostolic Signatura after receiving an annual report from individual tribunals, annual reports on the status and activities of the Tribunals. The new document of the Apostolic Signatura should undoubtedly improve and revive the dialogue of this Tribunal with the other ecclesiastical tribunals in the world.